Ignition study of high-energy materials containing Al, B, AlB2 and TiB2 powders - Korotkikh A. G. Aleksandr Gennadievich; Arkhipov V. A. Vladimir Afanasjevich; Slyusarsky K. V. Konstantin Vitaljevich; Sorokin I. V. Ivan Viktorovich (2017, 2017)
Title screen